The Impact of Government’s Foreign Debt on Fiscal Sustainability of Indonesia - Yohanes Maria Vianey Mudayen (International Journal of Economics and Financial Issues, 2017)
The aim of the research is to analyze the impact of government’s foreign debt on fiscal sustainability (FS) of Indonesia in 1979-2016. The model used in this research is a simultaneous equation model with the method of two stage least square. The simultaneous equation model regression results indicate that government foreign debt, FS which derives from the reduced-form equation and primary balance has a significant impact on the growth of economy in Indonesia positively. Government foreign debt lag and interest rate of Central Bank of Indonesia have a negative impact and it is significant toward the FS of Indonesia. However, the economic growth which comes from reduced form affect positively and have a significant impact on the FS of Indonesia.